2024
DOI: 10.3847/1538-4357/ad1f5b
|View full text |Cite
|
Sign up to set email alerts
|

Searches for Neutrinos in the Direction of Radio-bright Blazars with the ANTARES Telescope

A. Albert,
S. Alves,
M. André
et al.

Abstract: Active galaxies, especially blazars, are among the most promising extragalactic candidates for high-energy neutrino sources. To date, ANTARES searches included these objects and used GeV–TeV γ-ray flux to select blazars. Here, a statistically complete blazar sample selected by their bright radio emission is used as the target for searches of origins of neutrinos collected by the ANTARES neutrino telescope over 13 yr of operation. The hypothesis of a neutrino–blazar directional correlation is tested by pair cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Earlier statistical associations of neutrinos with bright blazars strongly link neutrino production to the very central parsec-scale regions of blazars [e.g., [9][10][11]13]. Still, observational…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Earlier statistical associations of neutrinos with bright blazars strongly link neutrino production to the very central parsec-scale regions of blazars [e.g., [9][10][11]13]. Still, observational…”
Section: Discussionmentioning
confidence: 99%
“…the neutrino association with radio blazars is starting to come from ANTARES [11] and Baikal-GVD [12] experiments. Additionally, [9] found that these high-energy neutrino events coincide with radio flares of the associated blazars, for which radio light curves are available.…”
Section: Jcap05(2024)133mentioning
confidence: 99%
See 1 more Smart Citation
“…An archival search of 9.5 yr of IceCube data found further evidence at a statistical significance of 3.5σ for a neutrino flare that occurred between 2014 September and 2015 March that was not coincident with gamma-ray emission (Aartsen et al 2018b). Since then, further searches (Allakhverdyan et al 2023;Albert et al 2024) have hinted at the possible connection of neutrino flares and blazars. IceCube observed evidence for continuous neutrino emission from the Seyfert galaxy NGC 1068 with a significance of 4.2σ (Abbasi et al 2022).…”
Section: Introductionmentioning
confidence: 99%